Hydrochemical characteristics and pollution potential of Uluova aquifers, Elazig, Turkey - Çetindag, B; Okan, ÖÖ (Springer-Verlag, 2004)
The study area is in the southeastern part of the city of Elazig between 38degrees17'-38degrees43' latitudes and 38degrees36'-39degrees07' longitudes. Formations of Paleozoic, Mesozoic and Cenozoic age comprise confined and unconfined aquifers. Unconfined aquifers are represented by Na-Cl and Na-HCO3 type waters while confined aquifers are characterized by Ca-HCO3, Mg-HCO3 and Na-HCO3 type waters. Due to sodium pollution, as a result of irrigation from waters of Hazar lake in the plain, as well as intense use of artificial fertilizer and improper storage of animal fertilizers, NH4-N, NO3-N and total PO4-P pollution are detected in waters of the unconfined aquifer. Organic material contents in waters of well nos. S-27, S-29 and S-32 completed in the unconfined aquifer are above 3.5 mg/l of Turkish Standard Institute (TSE), (266) standard. In confined aquifers, total PO4-P pollution in four wells and NH4-N pollution in three wells were observed to be above the TSE (266) standard.
Keywords: groundwater pollution; Uluova; Hazar lake; hydrochemical facies; wastewater treatment facility; Turkey